A Multicenter Study of Pediatric Macular Holes: Surgical Outcomes With Microincisional Vitrectomy Surgery. (January 2020) - Kothari, Nikisha; Read, Sarah P.; Baumal, Caroline R.; Capone, Antonio; Chang, Emmanuel; Drenser, Kimberly A.; Ferrone, Philip J.; Nudleman, Eric; Rao, Prethy; Sisk, Robert A.; Smiddy, William E.; Yonekawa, Yoshihiro; et al.
Purpose: Pediatric macular holes occur often related to trauma and rarely require surgical intervention. The purpose of the present study was to evaluate outcomes of microincisional vitrectomy surgery. Methods: A multicenter retrospective consecutive case series was conducted of pediatric patients undergoing surgery for macular hole repair. Results: A total of 31 eyes from 8 centers were included in this study. The mechanism of macular hole development was blunt trauma in 30 eyes (97%) and industrial laser in 1 eye (3%). The rate of anatomic closure after primary vitrectomy was 81% (25 eyes); the final anatomic closure rate after a secondary vitrectomy was 94% (29 eyes). There was a statistically significant improvement in visual acuity from initial presentation (20/164) to final follow-up (20/100) ( P = .009). Conclusions: Microincisional vitrectomy surgery for pediatric macular holes results in substantial anatomic success and modest improvement in visual acuity.